2018
DOI: 10.1128/aem.00715-18
|View full text |Cite
|
Sign up to set email alerts
|

Poikilothermic Animals as a Previously Unrecognized Source of Fecal Indicator Bacteria in a Backwater Ecosystem of a Large River

Abstract: Quantitative information regarding the presence of , intestinal enterococci, and in poikilotherms is notably scarce. Therefore, this study was designed to allow a systematic comparison of the occurrence of these standard fecal indicator bacteria (SFIB) in the excreta of wild homeothermic (ruminants, boars, carnivores, and birds) and poikilothermic (earthworms, gastropods, frogs, and fish) animals inhabiting an alluvial backwater area in eastern Austria. With the exception of earthworms, the average concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…Many water quality authorities rely on methods using general fecal indicator bacteria (FIB), such as culture-based Escherichia coli and enterococci, to determine if surface waters impacted by sewage are safe for swimming and other recreational activities. However, these cultivation-based procedures have several limitations, e.g., they typically require 18 h or more to yield results, making it challenging to ascertain water safety on the same day of use (7), the methods target bacteria when viral pathogens are thought to be the dominant public health risk in sewage pollution (8), and FIB are present in fecal waste across a broad range of animal groups (9), making it impossible to determine if sewage or another pollution source is the cause of water contamination.…”
mentioning
confidence: 99%
“…Many water quality authorities rely on methods using general fecal indicator bacteria (FIB), such as culture-based Escherichia coli and enterococci, to determine if surface waters impacted by sewage are safe for swimming and other recreational activities. However, these cultivation-based procedures have several limitations, e.g., they typically require 18 h or more to yield results, making it challenging to ascertain water safety on the same day of use (7), the methods target bacteria when viral pathogens are thought to be the dominant public health risk in sewage pollution (8), and FIB are present in fecal waste across a broad range of animal groups (9), making it impossible to determine if sewage or another pollution source is the cause of water contamination.…”
mentioning
confidence: 99%
“…However, recent studies have shown that E. coli can survive for long periods of time in soil, sand, sediment and water, in tropical, subtropical and temperate climates, which facilitates its dissemination in water supply systems and explains the increased contamination during rainy periods (Jang et al, 2017). In addition, Frick et al (2018) evaluated the abundance of E. coli in several groups of animals (homeothermic and poikilothermic), in an alluvial backwater in Austria, whose results showed the average concentrations of this bacterium in poikilothermic excreta, close to those found in homeothermic plants, confirming that its occurrence it is not exclusive to warm-blooded animals.…”
Section: Resultsmentioning
confidence: 99%
“…After incubation, FIB colonies were identified according to the agar manufacturer's protocol, in which dark blue colonies on CCA were scored as E. coli (Byamukama et al 2000), while fluorescing black colonies growing on F-TSC plates (Byamukama et al 2005) and round pink to dark maroon-coloured colonies on mENT plates were scored as CP and ENT, respectively. Of note, the detection limit (DL) for the considered faecal indicator bacteria in this study was 10 cfu/g for soil and 1 cfu/100 ml for water as determined according to the formula described by Frick et al (2018). The numbers of E. coli, ENT and CP colonies were separately quantified from their respective plates and were expressed as colony-forming units per 100 ml or gram for water or soil samples, respectively.…”
Section: Sampling Water and Soil For Sfib Analysesmentioning
confidence: 99%